Hubungan antara Intensitas Komunikasi Keluarga dan Tingkat Interaksi Teman Sebaya dengan Sikap Remaja Disabilitas Mental tentang Perilaku Seksual Pranikah - Maghfira Ainun F.; Agus Naryoso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The research has a purpose determines if there is a relations between The Intensity of Family Communication and The Level of Peer Interaction with Teenage Disability About Premarital Sexual Behavior. This research is a quantitative research using Reasoned Action Theory by Ajzen dan Fishbein and Reference Group Theory by Francis Bourne. Sampel this research is students with mental disabilities aged 10 to 19 years at SLBN Semarang. The sample was examined by 30 respondents. Based on the hypothetical analysis carried out by rank Kendall analysis, it shows that an intensity of family communication has to do with teenage disability attitudes on premarital sexuality behavior. It was based on a controlled correlation analysis. Significance by 0.025 < 0.05 and hypothesis accepted. And the value of 0.381 has the sense that an intensity of family communication with a teenage disability about premarital sexuality behavior has enough relationships. While on the variable level of peer interactions has a bearing on youth's mental disability attitude about premarital sexuality behavior. It was based on a controlled correlation analysis. The significance of 0,000 < 0.05 means an acceptable hypothesis. And the r value of 0.657 has the sense that increased family communication with teenage disability regarding premarital sexuality behavior has a strong relationship